2020
DOI: 10.3389/fpls.2020.606178
|View full text |Cite
|
Sign up to set email alerts
|

Potato Cyst Nematodes: Geographical Distribution, Phylogenetic Relationships and Integrated Pest Management Outcomes in Portugal

Abstract: The identification and phylogenetic relationships of potato cyst nematodes (PCN) were studied to assess the potential value of geographical distribution information for integrated pest management of potato production in Portugal. This research focused on PCN species, Globodera pallida and Globodera rostochiensis. From 2013 until 2019, 748 soil samples from the rhizosphere of different potato cultivars were surveyed in the Portuguese mainland to detect and identify both species and track their location. PCN are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…In this regard, only G. pallida or G. rostochiensis alone isolates in different regions (Algiers, Boumerdes, Blida, Tipaza, Béchar and El Oued) were identified by [ 19 ]. Similar investigations carried out in various other countries have shown the presence of alone isolates and mixed isolates of the PCN species [ 13 , 48 , 49 , 50 , 51 , 52 ], which corroborates with these results. In addition, according to [ 48 ], G. pallida and G. rostochiensis rarely occurred as separate species, but more often as a mixture species in the same field.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this regard, only G. pallida or G. rostochiensis alone isolates in different regions (Algiers, Boumerdes, Blida, Tipaza, Béchar and El Oued) were identified by [ 19 ]. Similar investigations carried out in various other countries have shown the presence of alone isolates and mixed isolates of the PCN species [ 13 , 48 , 49 , 50 , 51 , 52 ], which corroborates with these results. In addition, according to [ 48 ], G. pallida and G. rostochiensis rarely occurred as separate species, but more often as a mixture species in the same field.…”
Section: Discussionsupporting
confidence: 90%
“…Globodera pallida alone isolates are present in 44% of the fields prospected, while G. rostochiensis alone isolates and mixed isolates are present in the rest of the fields with equal proportions (28%), showing the dominance of the G. pallida species in potato fields. This may result from the control of populations of G. rostochiensis through the intensive cultivation of resistant potato cultivars as is occurring in other countries like the Netherlands [ 53 ], United Kingdom [ 54 , 55 , 56 ] and Portugal [ 52 ] since almost all current potato cultivars are resistant or tolerant to this species [ 34 ], unlike with G. pallida species where the number of resistant varieties is limited [ 26 , 34 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sequence alignment of the "3′end18S-ITS1-5.8S-ITS2-5′end28S" region of Portuguese isolates (G. pallida, G. rostochiensis and Globodera n. sp., the three predominant species in Portugal [52]) and several from the GeneBank database for G. pallida, G. rostochiensis, Globodera n. sp., G. mexicana and G. ellingtonae (Supplementary Table S1) was performed.…”
Section: Sequencing and Primer Designmentioning
confidence: 99%
“…The detection of the target species within pools of non-target species was attempted because it was previously demonstrated that G. pallida and G. rostochiensis cohabit in mixed populations in potato fields [52,56]. Samples of pure G. pallida and pure G. rostochiensis were not used since the specificity had been previously demonstrated.…”
Section: Diagnostic Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation